2017
DOI: 10.1088/1361-6595/aa62ee
|View full text |Cite
|
Sign up to set email alerts
|

Cathode voltage and discharge current oscillations in HiPIMS

Abstract: Thispaper reports on the oscillations both on the cathode voltage and on the discharge current which emerged suddenly and simultaneously during ahigh-power impulse magnetron sputtering pulse. Detailedexperiments identified the pressure and the discharge current ranges to detect these oscillations. The oscillationsoriginatedfrom the magnetized plasma and their frequency ranged from 225 kHz to 400 kHz depending on the experimental conditions. Simultaneous measurement of both oscillations and spokes was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 39 publications
5
18
0
Order By: Relevance
“…Considering the race track circumference of 14 cm and based on earlier measurements [26] the mode number of approximately 8 is expected. This provides us with the spoke velocity of about 5 km s −1 , which is in agreement with reports for similar pressures [44]. The range of the relative spoke size of 3-8 µs, which was chosen for the data processing, corresponds to the spoke mode number range of 4-9.…”
Section: Statistical Analysis Of the Relative Spoke Sizesupporting
confidence: 87%
See 1 more Smart Citation
“…Considering the race track circumference of 14 cm and based on earlier measurements [26] the mode number of approximately 8 is expected. This provides us with the spoke velocity of about 5 km s −1 , which is in agreement with reports for similar pressures [44]. The range of the relative spoke size of 3-8 µs, which was chosen for the data processing, corresponds to the spoke mode number range of 4-9.…”
Section: Statistical Analysis Of the Relative Spoke Sizesupporting
confidence: 87%
“…The generator is equipped with Melec Measurement System MS-500-D-TB for discharge current and cathode voltage measurements. To acquire a stable plateau of the discharge current, an 1 Ω ballast resistor was integrated into the HiPIMS generator output in series with a cathode [30,44]. Thus, the added resistor worked as negative feedback limiting the rise of the discharge current.…”
Section: Hipims Systemmentioning
confidence: 99%
“…F Avino https:/ /orcid.org/0000-0002-6206-0960 The large fraction of ionized sputtered atoms in plasmas obtained with High Power Impulse Magnetron Sputtering (HiPIMS) is making this technique very attractive for a constantly increasing number of fields [1][2][3][4][5][6]. The scientific community is devoting a significant effort to investigate and unveil the physical mechanisms of HiPIMS plasmas [7][8][9][10][11], as well as to explore the advantages with respect to well known sputtering techniques such as Direct Current Magnetron Sputtering (DCMS) [12,13]. Very recently, the effects of a positive voltage pulse (PP) applied to the target after the main negative pulse in the HiPIMS regime have started to be explored [14,15].…”
Section: Orcid Idsmentioning
confidence: 99%
“…A few years ago, it was observed that the plasma is not always homogeneously distributed over the racetrack area of the target in high-power impulse magnetron sputtering (HiPIMS) discharges [1][2][3], but under certain conditions it is self-organised into ionisation zones called spokes [2,4]. Several non-perturbing diagnostic techniques have been used to investigate spokes; these include photo-multiplier tubes [3,[5][6][7][8], high-speed 2D imaging of broadband emission [1][2][3][5][6][7][8][9][10][11][12][13][14][15][16][17][18], spectrally filtered high-speed 2D imaging [19][20][21], streak cameras [21][22][23][24], laser-induced fluorescence [20] and embedded probes [13,25,26]. Furthermore, more perturbing methods such as the Langmuir probe (single as well as multiprobe) [3,[5][6][7][8], emissive probe [2], magnetic sensor probe [27] or triple probe…”
Section: Introductionmentioning
confidence: 99%
“…The spoke mode number, i.e. the number of spokes, was studied for various target materials by different groups [5,7,9,10,14]. It was found that in different experimental configurations contradicting results may be obtained.…”
Section: Introductionmentioning
confidence: 99%